Citra Merek, Kualitas Produk, Harga dan Pengaruhnya terhadap Minat Beli Baju Karate Merek Arawaza di Kota Palembang - Puput Sekar Sari; Ninin Non Ayu Salmah (Universitas Batanghari Jambi, 2020)
The research objective was to determine the effect of brand image, product quality and price towards buying interest Arawaza brand karate clothes. This research is a quantitative and explanatory research. The population is athletes and trainers of karate athletes in Palembang City and wear karate baju from various brands in training activities and karate competitions both inside and outside the city of Palembang. The sampling technique is purposive sampling, namely athletes or athlete coaches who wear the Arawaza karate baju in training activities and karate competitions both inside and outside Palembang City. The number of samples was 58 respondents. The data used were primary data. The data collection technique is a questionnaire. The data analysis technique used is multiple linear regression with classical assumptions, the coefficient of determination and hypothesis testing. The result of this research is that simultaneously the brand image, product quality and price have a significant effect on buying interest, partially both brand image and product quality have a significant effect on buying interest and partially the price has no significant effect on the intention to buy Awaraza brand karate clothes. The regression equation concludes that brand image and product quality have a positive effect on purchase intention and price has a negative effect on purchase intention. The coefficient of determination shows that the variable brand image, product quality and price can explain the variable buying interest for Arawaza brand karate clothes by 90.1% while the remaining value of 9.9% is explained by other variables not involved in the research model.